2003
DOI: 10.1152/ajpheart.00725.2002
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic buffering affects cardiac bioenergetic signaling and contractile reserve similar to creatine kinase

Abstract: buffering affects cardiac bioenergetic signaling and contractile reserve similar to creatine kinase. Am J Physiol Heart Circ Physiol 285: H883-H890, 2003. First published April 24, 2003 10.1152/ajpheart.00725.2002 and glycolysis represent important energy-buffering processes in the cardiac myocyte. Although the role of compartmentalized CK in energy transfer has been investigated intensely, similar duties for intracellular glycolysis have not been demonstrated. By measuring the response time of mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…Indeed, our results showed that the ATP produced during prolonged ischemia contributed to sustain 60 % of control heart function at the end of reperfusion (Figure 4). Certainly, IAA is not a specific glycolytic inhibitor, but several reports indicate that a low concentration of IAA, as the one used here, neither inhibits other enzymes, such hexokinase, phosphofructokinase, pyruvate kinase [25], succinate dehydrogenase [26], nor does it inhibit mitochondrial oxidative capacity from reperfused hearts even at higher doses (e.g., 0.3 mM IAA) [27]. In this sense, we suggested that glycolysis also contributed to maintain the mechanical function at early reperfusion in the post-conditioned hearts, as the protective effect of the maneuver was significant inhibited in hearts in which iodoacetate was administered only during reperfusion.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, our results showed that the ATP produced during prolonged ischemia contributed to sustain 60 % of control heart function at the end of reperfusion (Figure 4). Certainly, IAA is not a specific glycolytic inhibitor, but several reports indicate that a low concentration of IAA, as the one used here, neither inhibits other enzymes, such hexokinase, phosphofructokinase, pyruvate kinase [25], succinate dehydrogenase [26], nor does it inhibit mitochondrial oxidative capacity from reperfused hearts even at higher doses (e.g., 0.3 mM IAA) [27]. In this sense, we suggested that glycolysis also contributed to maintain the mechanical function at early reperfusion in the post-conditioned hearts, as the protective effect of the maneuver was significant inhibited in hearts in which iodoacetate was administered only during reperfusion.…”
Section: Discussionmentioning
confidence: 73%
“…In studies utilizing iodoacetamide-induced creatine kinase (CK) inhibition (27,36) and CK knockout mice (25), muscle oxidative phosphorylation was activated more quickly than under control conditions when an active PCr system would normally buffer the increase in ADP. Glancy et al (19) demonstrated that the time constant of O 2 utilization by isolated mitochondrial preparations was related linearly to the total creatine (and PCr content) of the preparation.…”
Section: Discussionmentioning
confidence: 99%
“…IA affects not only CK-mediated energy flux but also glycolytic ATP production through inhibition of the glycolytic enzyme GAPDH (5,9,10,29). Thirteen percent of cardiomyocytes with 0.5 mM IA in the normal glucose concentration medium developed rigor contracture at 40 min [P Ͻ 0.05 by log-rank test; Fig.…”
Section: Cell Survival Experimentsmentioning
confidence: 99%
“…IA has been used by many investigators to inhibit CK (5,9,10,29) despite its lack of specificity. In fact, previous studies have demonstrated that 0.4 mM IA inhibited 70 -90% of the activity of the glycolytic enzyme GAPDH in the isolated perfused rat heart (9, 10), whereas activities of adenylate kinase (9, 10), hexokinase, and phosphofructokinase (5) were unaffected.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%